Bending analysis of carbon nanotube coated–fiber multi-scale composite beams using the refined zigzag theory - Malekimoghadam, Reza; Hosseini, Seyyed Ahmad; Icardi, Ugo (Aerospace Science and Technology, 2023)
The present work aims to investigate the bending analysis of sandwich and laminated carbon nanotube coated–fiber multi-scale composite (CFMC) beams employing the Refined Zigzag Theory (RZT). The model encompasses core fiber, surrounding carbon nanotube (CNT) coating region, and polymer matrix covering all scales from nano to macro-scale. Hierarchical multi-scale modeling is utilized where information is only transmitted from the fine-scale to the next coarser scale. The CNT coating region (CCR) consists of CNT, matrix, and non-bonded interphase whose mechanical properties are determined employing the Eshelby–Mori–Tanaka method and the equivalent continuum fiber approach. Considering different configurations of grown CNTs around the core fiber, two CCRs are constructed, comprising axially aligned (ACCR) and randomly oriented CCRs (RNCCR). The mechanical properties of the core fiber coated with the surrounding CCR are then obtained through the composite cylinder assemblage (CCA) method. Consequently, four RZT kinematic variables are acquired for the CFMC beams, and the effects of CNT volume fraction, coating thickness, and coating types are thoroughly investigated for various laminated and sandwich beams. The results reveal a substantial reduction in the maximum transverse displacements of the CFMC beams compared to the conventional composite beams, considering the low volume fraction of the CNTs in the coating region. Moreover, by employing a combination of ACCR and RNCCR for the layers in the sandwich CFMC beams, a pronounced decline in the transverse shear stress of the core medium is demonstrated, which can postpone the core shear failure in the sandwich structures. A great agreement is observed between the obtained results and the outcomes predicted by finite element analysis.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Bending analysis; CNT coated–fibers; Multi–scale hybrid composite beam; Refined Zigzag Theory (RZT)